T-tube ileostomy for intestinal perforation in extremely low birth weight neonates - Rygl, Michal; Pýcha, Karel; Straňák, Zbyněk; Škába, Richard; Brabec, Radim; Čunát, Václav; Šnajdauf, Jiří (Pediatric surgery international, 2007)
To evaluate the results of use of T-tube ileostomy in selected cases of intestinal perforation in extremely low birth weight (ELBW) neonates. The records of 288 ELBW neonates treated at author's institution, from 1998 to 2003 were retrospectively reviewed to identify neonates operated for intestinal perforation with T-tube placement. T-tube was inserted into the bowel through the site of perforation or proximally to the perforated gut via separate stab incision. T-tubes were used in five ELBW neonates (BW 600-900 g, gestational age 25-27 weeks) with intestinal perforation, in four of them at the time of primary surgery and in one neonate 8 days after primary anastomosis. All patients survived and there were no serious complications related to the T-tube insertion. Median duration of T-tube placement was 4 weeks (range 3-8 weeks), full enteral feeding after T-tube insertion was achieved in 4 weeks (range 1-6 weeks). All sites of T-tube insertion closed spontaneously. T-tube ileostomy is an effective and safe technique for treatment of selected cases of intestinal perforation in ELBW neonates. With respect to the hypoperistalsis of immature bowel, we recommend the use of T-tube in all cases of isolated intestinal perforation in ELWB neonates.
Keywords: novorozenec; Treatment Outcome; Retrospective Studies; novorozenec s extrémně nízkou porodní hmotností; lidé; Risk Factors; Female; výsledek terapie; financování organizované; Intestinal Perforation; Ileostomy; Male; ženské pohlaví; Humans; mužské pohlaví; Infant, Extremely Low Birth Weight; Financing, Organized; perforace střeva; ileostomie; Infant, Newborn; rizikové faktory; retrospektivní studie